Effect of Consumption of a Liquid Apple Yeast Additive on Growing-Finishing Pigs - Plascencia, Daniel Díaz; Flores, Pablo Fidel Mancillas; Baquera, Perla Lucía Ordóñez; Prieto, José Roberto Espinoza; Valdez, José Luis Guevara; Yáñez, Rosario Martínez (Migration Letters, 2023)
A liquid apple yeast additive (ALL) was evaluated on the productive behavior of pigs in the growth-completion stage. Four levels of ALL kg−1 of food from the diet were tested: 0 mL kg−1 (T1: control), 50 mL kg−1 (T2), 100 mL kg−1 (T3) and 150 mL kg−1 (T4). A total of 24 pigs with an average age of 30 days and a Average starting weight of 28,170 ± 3.6 kg. The variables evaluated were: live weight (BW), daily feed intake (CAD), daily weight gain (GDP), feed conversion (CAT), carcass yield (CR), rib eye area (COC), back fat thickness (EGD), meat and fat color (L, a*, b*) and blood count (BH). A univariate analysis was performed to detect statistical differences between treatments using a confidence level of α = 0.05. T3 was better (P < 0.05) for PV, GDP, CDA, and CA. (P < 0.01) for AOC, EGD and BH. It is concluded that the addition of 100 mL of ALL per kg of feed in the growth-completion diet of pigs improves their productive response and the health of the animals.